Pengaruh pH dan Waktu Kontak Terhadap Adsorpsi Ion Pb2+ pada Silika Gel-GPTMS Termodifikasi Sulfonat - Afrilia, Yoni; Oktavia, Budhi; Kurniawati, Desy; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Adsorption is the process of accumulation of atoms or ions in solution on the surface of a solid adsorbent. Silica gel can be used as an adsorbent because it has two groups of active sites, namely silanol (Si-OH) and siloxane (Si-O-Si). The active groups also allow silica to be modified. This modification was made to increase the ability of silica to adsorb ions, one of which is Pb2+ ion. The modifier compound used is a sulfonic salt (4-amino-5-hydroxy-2,7-naphthalenedisulfonic acid) with a glysidoxypropyltrimethoxysilane (GPTMS) linking compound. The modified adsorbents were characterized by FTIR and the absorption results were characterized by AAS. The modified adsorbent was to determine the optimum conditions for adsorption of Pb2+ ions using silica sulfonate. Adsorption was carried out using the batch method. The optimum absorption conditions for Pb2+ metal ions using silica sulfonate were obtained at pH 3, contact time of 45 minutes.